Evaluation of Stock Returns Against Systematic Risk Using the Capital Market Line (CML) Approach: An Empirical Study on LQ45 Stocks: English - Suhandi, Ni Putu Mila; Priyanto, Panji (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to evaluate the performance of LQ45 stocks against systematic risk using the Capital Market Line (CML) approach. The CML, derived from the Capital Asset Pricing Model (CAPM), represents the risk-return relationship between efficient portfolios and the market portfolio, incorporating both the risk-free rate and the total risk (standard deviation). Unlike the Security Market Line (SML), which uses beta as a measure of systematic risk, the CML emphasizes total risk in the context of portfolio efficiency. This research employs a quantitative descriptive method, analyzing secondary data of LQ45 constituents listed on the Indonesia Stock Exchange (IDX) for the period from January 2023 to December 2024. The Sharpe Ratio was calculated to assess the performance of individual stocks, followed by comparison with the CML benchmark. The findings reveal that only a limited number of stocks demonstrate efficiency by lying above CML, while the majority fall below, indicating suboptimal risk-adjusted returns. These results support the theoretical proposition that in efficient markets, only well-diversified portfolios, not individual assets, can consistently align with the CML. This study contributes to the growing literature on asset pricing by emphasizing the role of total risk in portfolio evaluation and provides practical implications for investors in constructing efficient portfolios.